Frida Kahlo, sobre vestido y cuerpo en psicoanálisis (2021)
This article approaches the work of the artist Frida Kahlo considering the function of semblance, the dress and the body in psychoanalysis. This work, developed through the method of deciphering proposed by Jacques Lacan, involves two moments: in the first one, the dress and the semblance, the function of Tehuana’s costume and its relation with the Lacanian syntagma: The woman does not exist; in the second one, The body and the birth of the artist, the imaginary dimension of the body and the configuration of identity in the creative act are highlighted